Hydrophobic hexagonal boron nitride chlorinated rubber composite coating and preparation method thereof
By using specific ratio additives and the preparation steps of regulating nanomaterials in hexagonal boron nitride chlorinated rubber composite coatings, the problem of poor hydrophobic properties of the coating is solved, and higher hydrophobicity and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202410709842.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The existing hexagonal boron nitride chlorinated rubber composite coatings fail to fully utilize the surface energy control ability of hexagonal boron nitride, resulting in poor hydrophobic properties of the coating.
By adding specific proportions of dispersants, plasticizers, thickeners, stabilizers and defoamers to the preparation of hydrophobic hexagonal boron nitride chlorinated rubber composite coatings, and controlling the two-dimensional nanomaterials of hexagonal boron nitride The peeling time in the preparation step is to construct a nano-scale surface defect structure and improve the hydrophobicity of the coating.
The hydrophobic properties and corrosion resistance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating are significantly improved, ensuring the stability and performance optimization of the coating.
Smart Images

Figure CN119242089A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the technical field of chemical coatings, and in particular to a hydrophobic hexagonal boron nitride chlorinated rubber composite coating and a preparation method thereof. Background Art
[0002] Chlorinated rubber is a chlorinated polymer obtained by chlorination modification of natural rubber or synthetic rubber. It has excellent film-forming properties, adhesion, and corrosion resistance. It is widely used in the manufacture of ship paints, chemical anti-corrosion paints, architectural coatings, etc. It is one of the promising chlorine-based fine chemical products. The traditional chlorinated rubber resin production process uses CCl4 solvent, which is an ozone-depleting substance that pollutes the atmosphere and is subject to environmental protection restrictions in various countries. In order to avoid pollution, it is necessary to develop a green production method for non-carbon tetrachloride anhydrous chlorinated rubber. At present, there is a method of using chloroform as a solvent to produce chlorinated rubber through liquid phase chlorination. This method does not require the use of CCl4 solvent and is reliable and environmentally friendly, but in actual use, the hydrophobicity of the chlorinated rubber coating prepared by this method still needs to be improved.
[0003] Two-dimensional nanomaterials have excellent surface energy regulation properties, and have great application potential in the preparation of hydrophobic coatings by using two-dimensional nanomaterials as modified hydrophobic materials. Hexagonal boron nitride two-dimensional nanomaterials are a layered material, which is stacked by covalently bonded B and N through weak van der Waals forces, and has physical and chemical properties such as high hydrophobicity, oxidation resistance, and high chemical stability. At present, some methods for preparing hydrophobic hexagonal boron nitride nanosheets realize the one-pot method of exfoliation and hydrophobic modification of boron nitride nanosheets, and at the same time achieve a high yield of hydrophobic hexagonal boron nitride nanosheets, but the dispersibility of hydrophobic hexagonal boron nitride nanosheets in polymers is poor, which is not conducive to use as coating fillers. At the same time, some methods for large-scale preparation of hydrophobic hexagonal boron nitride nanosheets have the advantages of simple process, low raw material cost, high yield, and easy to achieve mass production. The hydrophobic hexagonal boron nitride nanosheets produced by this method can be evenly dispersed in the polymer, but after being compounded with the coating, the overall surface energy regulation is insufficient, and the full potential of the hydrophobic hexagonal boron nitride nanosheets is not fully utilized.
[0004] Therefore, it is urgent to develop a hydrophobic hexagonal boron nitride chlorinated rubber composite coating that can fully utilize the surface energy regulation ability of hexagonal boron nitride and comprehensively improve the hydrophobic properties of chlorinated rubber coatings. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] The technical problem to be solved by the present invention is to solve the technical problem that the existing hexagonal boron nitride chlorinated rubber composite coating does not fully utilize the surface energy regulation ability of hexagonal boron nitride and the coating has poor hydrophobic performance.
[0007] (II) Technical solution
[0008] In order to solve the above technical problems, the present invention provides a hydrophobic hexagonal boron nitride chlorinated rubber composite coating on the one hand, and the preparation raw materials include: chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer and solvent; wherein the mass fraction ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoamer and the solvent is (80-100):(6-24):(20-40):(20-40):(20-60):(10-60):(20-50):(10-30):(10-50):(100-500).
[0009] In one embodiment, the mass ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoaming agent and the solvent is 100:12:30:30:50:40:30:20:20:200, or 100:6:30:30:50:40:30:20:20:200, or 100:12:20:20:30:30:20:10:10:100, or 100:18:40:40:60:50:40:30:30:30:30, or 100:24:30:30:50:40:30:20:20:200.
[0010] In one embodiment, the chlorinated rubber resin is a chlorinated rubber resin with a chlorine mass fraction between 66% and 68%, and the average relative molecular weight of the chlorinated rubber resin is 10,000 to 20,000; the dispersant is any one of polyethylene glycol 200 or polyethylene glycol 400 or a mixture thereof; the plasticizer is any one of dioctyl phthalate or dibutyl phthalate or a mixture thereof; the thickener is a mixture of methyl hydroxypropyl cellulose and bentonite; the stabilizer is any one of dibutyltin dilaurate or methyltin mercaptan or a mixture thereof; the defoamer is any one of a polyether defoamer or a silicone defoamer; the solvent is any one of acetone, xylene, and ethyl acetate or a mixture of two or more combinations thereof.
[0011] In one embodiment, the chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68%, and the average relative molecular weight of the chlorinated rubber resin is 12000; the dispersant is polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:2; the plasticizer is dioctyl phthalate and dibutyl phthalate in a mass ratio of 1:1; the thickener is methyl hydroxypropyl cellulose and bentonite in a mass ratio of 1:1; the stabilizer is dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:2; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene, and ethyl acetate in a mass ratio of 3:2:3.
[0012] On the other hand, the present invention also provides a method for preparing any of the above-mentioned hydrophobic hexagonal boron nitride chlorinated rubber composite coatings, comprising using hexagonal boron nitride two-dimensional nanomaterial powder as filler, and compounding it with chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer, and solvent in a preset ratio to prepare composite coating component one and component two respectively, mixing component one and component two evenly, performing film-forming treatment, and then curing at room temperature to obtain a hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0013] In one embodiment, the hexagonal boron nitride two-dimensional nanomaterial powder is used as a filler, and is compounded with a chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate, a dispersant, a plasticizer, a thickener, a stabilizer, a defoamer, and a solvent according to a preset ratio to prepare a composite coating component one and a component two respectively, and the component one and the component two are mixed evenly, subjected to a film-forming treatment, and then cured at room temperature to obtain a hydrophobic hexagonal boron nitride chlorinated rubber composite coating, including: grinding, high-speed dispersing, and filtering the chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial, hydroxymethyl acrylamide, ethyl acrylate, and a dispersant to obtain the hexagonal boron nitride chlorinated rubber composite coating component one; grinding, high-speed dispersing, and filtering the plasticizer, a thickener, a stabilizer, a defoamer, and a solvent to obtain the hexagonal boron nitride chlorinated rubber composite coating component two; mixing the obtained hexagonal boron nitride chlorinated rubber composite coating component one and component two evenly, conducting a film-forming treatment, and then curing at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating.
[0014] In one embodiment, the preparation process of the hexagonal boron nitride two-dimensional nanomaterial powder is as follows: using ammonium borate and urea to perform hydrothermal synthesis with programmed temperature, and obtaining a hexagonal boron nitride precursor after atmosphere protection and pickling process treatment; performing cell crushing and ultrasonic peeling on the hexagonal boron nitride precursor, and obtaining a hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure and a hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure by controlling the peeling time;
[0015] In one embodiment, the hydrothermal synthesis using ammonium borate and urea for programmed temperature is carried out to obtain a hexagonal boron nitride precursor after atmosphere protection and pickling process treatment, including: mixing ammonium borate and urea, stirring evenly, placing in a stainless steel reactor, heating to 80-100°C, keeping warm for 1-2h, then heating to 120-150°C, keeping warm for 1-2h, heating to 160-180°C, passing nitrogen, and pickling the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor.
[0016] In one embodiment, the mass ratio of the ammonium borate to the urea is 2:3.
[0017] In one embodiment, the hexagonal boron nitride precursor is subjected to cell crushing and ultrasonic exfoliation, and the hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure and the hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure are obtained by controlling the exfoliation time, including: weighing the hexagonal boron nitride precursor and adding it to a beaker, then adding deionized water and isopropanol, stirring with a stirrer to mix it evenly, sealing the beaker mouth and placing it in an ultrasonic cleaning machine for 1 to 2 hours to fully disperse the hexagonal boron nitride precursor powder. The beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion is placed in a cell crusher, and the total exfoliation time is 4 to 18 hours. The dispersion obtained by crushing and exfoliation is centrifuged at a speed of 5000r / min and the upper clear liquid is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder.
[0018] In one embodiment, the mass ratio of the hexagonal boron nitride precursor, the deionized water and the isopropyl alcohol is 1:(2-3):(2-3).
[0019] In one embodiment, when the stripping time is controlled to be 6 hours or less, a hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure is obtained; when the stripping time is controlled to be greater than 6 hours, a hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure is obtained.
[0020] (III) Beneficial effects
[0021] The above technical solution of the present invention has the following advantages:
[0022] In this embodiment, a dispersant, a plasticizer, a thickener, and a stabilizer in a specific ratio are added during the preparation of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating, so that the mixing between the raw materials of the composite coating is faster and more uniform, which is beneficial to improving the performance stability of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating; the defoaming agent can reduce the generation of bubbles during the mixing of the raw materials, avoid the problem of internal voids caused by bubbles in the prepared hydrophobic hexagonal boron nitride chlorinated rubber composite coating, and is beneficial to improving the corrosion resistance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0023] In the present embodiment, in the process of preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating, the stripping time of the hexagonal boron nitride two-dimensional nanomaterial preparation step is regulated, and a nanoscale surface defect structure is constructed on the surface of the hexagonal boron nitride by chemical means to achieve the effect of surface functionalization. These defect structures can regulate the surface energy of the hexagonal boron nitride two-dimensional nanomaterial, thereby improving the hydrophobicity of the hexagonal boron nitride chlorinated rubber composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the morphology of a hydrophobic hexagonal boron nitride two-dimensional nanomaterial according to an embodiment of the present invention;
[0025] Figure 2 This is an example diagram of the element distribution of hydrophobic hexagonal boron nitride according to an embodiment of the present invention;
[0026] Figure 3 A schematic diagram showing the comparison of the microscopic morphology of hexagonal boron nitride with no surface defect structure and hexagonal boron nitride with rich surface defect structure according to an embodiment of the present invention;
[0027] Figure 4 Schematic diagram of contact angles of various embodiments of the present invention. DETAILED DESCRIPTION
[0028] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0030] The following detailed description of the embodiments of the present invention is provided in conjunction with the accompanying drawings and examples. The following detailed description of the embodiments and the accompanying drawings are used to illustrate the principles of the present invention, but cannot be used to limit the scope of the present invention, that is, the present invention is not limited to the described embodiments.
[0031] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0032] Before introducing the present embodiment, the reasons why the existing hexagonal boron nitride chlorinated rubber composite coating has poor hydrophobicity are first introduced. Specifically:
[0033] 1. Dispersion of hexagonal boron nitride in chlorinated rubber
[0034] Hexagonal boron nitride nanosheets have a large surface area. When added to chlorinated rubber as a functional filler, the electrostatic force, van der Waals force, and chemical bond between particles tend to reduce the surface area and cause agglomeration. The agglomeration of hexagonal boron nitride nanosheets in chlorinated rubber will reduce the crosslinking degree of the chlorinated rubber, resulting in defects such as microcracks and holes in the coating, which will have a negative impact on the physical shielding and hydrophobic properties of the coating.
[0035] 2. The hydrophobic properties of hexagonal boron nitride are difficult to fully exert and maintain in composite coatings
[0036] The mechanism of hydrophobicity is closely related to the special orientation and arrangement of water molecules at the hydrophobic interface. Since the hydrophobic surface has no or very weak hydrogen bond forming ability, it will force some of the interfacial water molecules to change their original orientation and form a certain number of "dangling" hydrogen-oxygen bonds perpendicular to the hydrophobic surface. These fixed-direction dipoles drive the surrounding water molecules to rearrange into a relatively regular and orderly hydration layer through a dynamic hydrogen bond network. The formation of this orderly network of interfacial water molecules will lead to a significant decrease in entropy, which is thermodynamically unfavorable. Therefore, hydrophobic substances tend to aggregate with each other in water to reduce the number of interfacial water molecules, increase system entropy, and reduce the system surface free energy to maintain hydrophobic properties. Unlike graphene oxide materials that have many oxygen-containing functional groups (hydroxyl, carboxyl, epoxy, etc.) on the surface, hexagonal boron nitride has almost no functional groups on the surface. After the hydrophobic hexagonal boron nitride and chlorinated rubber are compounded, it is not conducive to exerting its surface hydrophobic properties in the composite coating system. The polymer main chain in the system is easily affected by external factors (light, water, oxygen and chemicals), which affects the service life of the composite coating.
[0037] In view of the above reasons, this embodiment adds a specific ratio of dispersant, plasticizer, thickener and stabilizer in the process of preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating, so that the mixing between the raw materials of the composite coating is faster and more uniform, which is beneficial to improving the performance stability of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating; the defoaming agent can reduce the generation of bubbles in the process of mixing the raw materials, avoid the problem of internal voids caused by bubbles in the prepared hydrophobic hexagonal boron nitride chlorinated rubber composite coating, which is beneficial to improving the corrosion resistance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0038] In addition, this embodiment achieves the effect of surface functionalization by regulating the stripping time of the preparation step of the hexagonal boron nitride two-dimensional nanomaterial in the process of preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating, constructing a special defect structure on the surface of the hexagonal boron nitride two-dimensional nanomaterial, so as to improve the hydrophobic performance of the hexagonal boron nitride, and at the same time, the hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure can fully exert its hydrophobic effect in the composite coating. The surface defect structure provides abundant dangling bonds on the surface of the hexagonal boron nitride two-dimensional nanomaterial, which can improve the dispersibility and compatibility of the hexagonal boron nitride two-dimensional nanomaterial in the composite coating system, and is embedded in the cross-linked network of the entire chlorinated rubber. At the same time, the surface defect structure will bring about changes in the local electronic structure, regulate the local charge density, strengthen the hydrophobic performance of the hexagonal boron nitride, and improve the comprehensive performance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0039] The present embodiment will be described in detail below.
[0040] Overall embodiment
[0041] A hydrophobic hexagonal boron nitride chlorinated rubber composite coating, the raw materials for preparation include: chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer and solvent;
[0042] Among them, the mass ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoaming agent and the solvent is (80-100):(6-24):(20-40):(20-40):(20-60):(10-60):(20-50):(10-30):(10-50):(100-500).
[0043] Here, in actual application, the mass ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoaming agent and the solvent can be specifically selected as 100:12:30:30:50:40:30:20:20:200, or 100:6:30:30:50:40:30:20:20:200, or 100:12:20:20:30:30:20:10:10:100, or 100:18:40:40:60:50:40:30:30:30:30, or 100:24:30:30:50:40:30:20:20:200.
[0044] The chlorinated rubber resin in this embodiment may be a chlorinated rubber resin having a chlorine mass fraction of 66% to 68%, and the average relative molecular weight of the chlorinated rubber resin may be 10,000 to 20,000; the dispersant may be any one of polyethylene glycol 200 or polyethylene glycol 400 or a mixture thereof; the plasticizer may be any one of dioctyl phthalate or dibutyl phthalate or a mixture thereof; the thickener may be a mixture of methyl hydroxypropyl cellulose and bentonite; the stabilizer may be any one of dibutyltin dilaurate or methyltin mercaptan or a mixture thereof; the defoamer may be any one of a polyether defoamer or a silicone defoamer; the solvent may be any one of acetone, xylene, ethyl acetate or a mixture of two or more thereof.
[0045] In practical application, the chlorinated rubber resin can be specifically selected from chlorinated rubber resins with a chlorine mass fraction of 66% to 68%, and the average relative molecular weight of the chlorinated rubber resin is 12000; the dispersant can be specifically selected from polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:2; the plasticizer can be specifically selected from dioctyl phthalate and dibutyl phthalate in a mass ratio of 1:1; the thickener can be specifically selected from methyl hydroxypropyl cellulose and bentonite in a mass ratio of 1:1; the stabilizer can be specifically selected from dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:2; the defoamer can be specifically selected from a polyether defoamer; and the solvent can be specifically selected from a mixture of acetone, xylene, and ethyl acetate in a mass ratio of 3:2:3.
[0046] In this embodiment, a dispersant, a plasticizer, a thickener, and a stabilizer in a specific ratio are added during the preparation of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating, so that the mixing between the raw materials of the composite coating is faster and more uniform, which is beneficial to improving the performance stability of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating; the defoaming agent can reduce the generation of bubbles during the mixing of the raw materials, avoid the problem of internal voids caused by bubbles in the prepared hydrophobic hexagonal boron nitride chlorinated rubber composite coating, and is beneficial to improving the corrosion resistance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0047] Furthermore, the preparation method of any of the above-mentioned hydrophobic hexagonal boron nitride chlorinated rubber composite coatings in this embodiment is:
[0048] Ammonium borate and urea are used for programmed temperature hydrothermal synthesis, and after atmosphere protection and pickling process treatment, a hexagonal boron nitride precursor is obtained. The hexagonal boron nitride precursor is subjected to cell crushing and ultrasonic exfoliation, and a hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure and a hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure are obtained by controlling the exfoliation time. The prepared hexagonal boron nitride two-dimensional nanomaterial powder is used as a filler, and is compounded with chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer, and solvent in a specific ratio to prepare composite coating component one and component two respectively. Component one and component two are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain the desired coating.
[0049] The specific technical solution mainly includes 5 steps:
[0050] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80-100°C, keep warm for 1-2 hours, then heat to 120-150°C, keep warm for 1-2 hours, heat to 160-180°C, introduce nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2-3 parts of deionized water and 2-3 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1-2 hours to fully disperse the hexagonal boron nitride precursor powder. A beaker containing a uniformly mixed hexagonal boron nitride precursor dispersion is placed in a cell crusher. The total peeling time is 4 to 18 hours. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000 r / min and the upper clear liquid is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion. After filtering and drying, hexagonal boron nitride two-dimensional nanomaterial powder is obtained.
[0051] 2. Prepare the following raw materials in parts by mass: 80-100 parts of chlorinated rubber resin; 6-24 parts of hexagonal boron nitride two-dimensional nanomaterials; 20-40 parts of hydroxymethyl acrylamide; 20-40 parts of ethyl acrylate; 20-60 parts of dispersant; 10-60 parts of plasticizer; 20-50 parts of thickener; 10-30 parts of stabilizer; 10-50 parts of defoaming agent; 100-500 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine mass fraction of 66% to 68% and an average relative molecular weight of 10,000 to 20,000; the dispersant is any one of polyethylene glycol 200 or polyethylene glycol 400 or a mixture thereof; the plasticizer is any one of dioctyl phthalate or dibutyl phthalate or a mixture thereof; the thickener is a mixture of methyl hydroxypropyl cellulose and bentonite; the stabilizer is any one of dibutyltin dilaurate or methyltin mercaptan or a mixture thereof; the defoamer is any one of a polyether defoamer or a silicone defoamer; and the solvent is any one of acetone, xylene, and ethyl acetate or a mixture of two or more combinations thereof.
[0052] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterials, hydroxymethyl acrylamide, ethyl acrylate, and dispersant according to the ratio, and obtain hexagonal boron nitride chlorinated rubber composite coating component 1 through grinding, high-speed dispersion, and filtration.
[0053] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating.
[0054] 5. The obtained hexagonal boron nitride chlorinated rubber composite coating component 1 and component 2 are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain a hexagonal boron nitride chlorinated rubber composite coating.
[0055] Here, when the stripping time is controlled to be 6 hours or less, a hexagonal boron nitride two-dimensional nanomaterial powder with a surface defect-free structure can be obtained; when the stripping time is controlled to be greater than 6 hours, a hexagonal boron nitride two-dimensional nanomaterial powder with a surface defect-rich structure can be obtained.
[0056] When implementing the application, it is recommended to control the stripping time to more than 6 hours to obtain hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure, and use the hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure to prepare hexagonal boron nitride chlorinated rubber composite coating, which can make the hexagonal boron nitride chlorinated rubber composite coating have better hydrophobic properties.
[0057] This embodiment achieves the effect of surface functionalization by regulating the stripping time of the preparation step of hexagonal boron nitride two-dimensional nanomaterials in the process of preparing hydrophobic hexagonal boron nitride chlorinated rubber composite coatings, constructing a special defect structure on the surface of hexagonal boron nitride two-dimensional nanomaterials, so as to improve the hydrophobic properties of hexagonal boron nitride, and at the same time, make the hexagonal boron nitride two-dimensional nanomaterial powder rich in surface defect structure fully exert its hydrophobic effect in the composite coating. The surface defect structure provides abundant dangling bonds on the surface of hexagonal boron nitride two-dimensional nanomaterials, which can improve the dispersibility and compatibility of hexagonal boron nitride two-dimensional nanomaterials in the composite coating system, and embed into the cross-linked network of the entire chlorinated rubber. At the same time, the surface defect structure will bring about changes in the local electronic structure, regulate the local charge density, strengthen the hydrophobic properties of hexagonal boron nitride, and improve the comprehensive performance of the hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
[0058] Embodiment 1:
[0059] 1. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 30 parts of hydroxymethyl acrylamide; 30 parts of ethyl acrylate; 50 parts of dispersant; 40 parts of plasticizer; 30 parts of thickener; 20 parts of stabilizer; 20 parts of defoamer; 200 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:1; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 2:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 2:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:1; the defoamer is a polyether defoamer; the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 1:2:1.
[0060] 2. Prepare chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, grind, high-speed disperse and filter to obtain chlorinated rubber coating component 1.
[0061] 3. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, and obtain chlorinated rubber coating component 2 by grinding, high-speed dispersion and filtration.
[0062] 4. The obtained chlorinated rubber coating component 1 and component 2 are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain a chlorinated rubber coating.
[0063] Embodiment 2:
[0064] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80°C, keep warm for 1h, then heat to 120°C, keep warm for 1h, heat to 160°C, pass nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2 parts of deionized water and 2 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1h to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 6h. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min and the supernatant is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, filter, and dry to obtain a hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure.
[0065] 2. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 12 parts of hexagonal boron nitride two-dimensional nanomaterial with no surface defect structure; 30 parts of hydroxymethyl acrylamide; 30 parts of ethyl acrylate; 50 parts of dispersant; 40 parts of plasticizer; 30 parts of thickener; 20 parts of stabilizer; 20 parts of defoaming agent; and 200 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:1; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 2:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 2:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:1; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 1:2:1.
[0066] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial with no surface defect structure, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, and obtain component 1 of hexagonal boron nitride chlorinated rubber composite coating with no surface defect structure through grinding, high-speed dispersion and filtration.
[0067] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating with no surface defect structure.
[0068] 5. The obtained hexagonal boron nitride chlorinated rubber composite coating with no surface defect structure, component 1 and component 2 are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain a hexagonal boron nitride chlorinated rubber composite coating with no surface defect structure.
[0069] Embodiment three:
[0070] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80°C, keep warm for 1h, then heat to 120°C, keep warm for 1h, heat to 160°C, pass nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2 parts of deionized water and 2 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1h to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 12h. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min and the supernatant is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder with a rich surface defect structure.
[0071] 2. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 6 parts of hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure; 30 parts of hydroxymethyl acrylamide; 30 parts of ethyl acrylate; 50 parts of dispersant; 40 parts of plasticizer; 30 parts of thickener; 20 parts of stabilizer; 20 parts of defoaming agent; 200 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:1; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 2:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 2:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:1; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 1:2:1.
[0072] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, and obtain component 1 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure through grinding, high-speed dispersion and filtration.
[0073] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0074] 5. The obtained component one and component two of the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure are evenly mixed, subjected to film-forming treatment, and then cured at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0075] Embodiment 4:
[0076] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80°C, keep warm for 1h, then heat to 120°C, keep warm for 1h, heat to 160°C, pass nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2 parts of deionized water and 2 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1h to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 12h. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min and the supernatant is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder with a rich surface defect structure.
[0077] 2. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 12 parts of hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure; 20 parts of hydroxymethyl acrylamide; 20 parts of ethyl acrylate; 30 parts of dispersant; 30 parts of plasticizer; 20 parts of thickener; 10 parts of stabilizer; 10 parts of defoaming agent; 100 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:1; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 2:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 2:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:1; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 1:2:1.
[0078] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, and obtain component 1 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure through grinding, high-speed dispersion and filtration.
[0079] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0080] 5. The obtained component one and component two of the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure are evenly mixed, subjected to film-forming treatment, and then cured at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0081] Embodiment five:
[0082] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80°C, keep warm for 1h, then heat to 120°C, keep warm for 1h, heat to 160°C, pass nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2 parts of deionized water and 2 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1h to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 12h. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min and the supernatant is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder with a rich surface defect structure.
[0083] 2. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 18 parts of hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure; 40 parts of hydroxymethyl acrylamide; 40 parts of ethyl acrylate; 60 parts of dispersant; 50 parts of plasticizer; 40 parts of thickener; 30 parts of stabilizer; 30 parts of defoaming agent; 300 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:1; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 2:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 2:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:1; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 1:2:1.
[0084] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, and obtain component 1 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure through grinding, high-speed dispersion and filtration.
[0085] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0086] 5. The obtained component one and component two of the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure are evenly mixed, subjected to film-forming treatment, and then cured at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0087] Embodiment six:
[0088] 1. Mix 2 parts of ammonium borate and 3 parts of urea, stir evenly, place in a stainless steel reactor, heat to 80°C, keep warm for 1h, then heat to 120°C, keep warm for 1h, heat to 160°C, pass nitrogen, and pickle the reaction product with hydrochloric acid to obtain a hexagonal boron nitride precursor. Weigh 1 part of the hexagonal boron nitride precursor and add it to a beaker, then add 2 parts of deionized water and 2 parts of isopropanol, stir with a stirrer to mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1h to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 18h. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min and the supernatant is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder with a rich surface defect structure.
[0089] 2. Prepare the following raw materials in parts by mass: 100 parts of chlorinated rubber resin; 24 parts of hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure; 30 parts of hydroxymethyl acrylamide; 30 parts of ethyl acrylate; 50 parts of dispersant; 40 parts of plasticizer; 30 parts of thickener; 20 parts of stabilizer; 20 parts of defoaming agent; and 200 parts of solvent. The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68% and an average relative molecular weight of 12,000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:2; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 1:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 1:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:2; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 3:2:3.
[0090] 3. Prepare chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial with rich surface defect structure, hydroxymethyl acrylamide, ethyl acrylate and dispersant according to the ratio, and obtain component 1 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure through grinding, high-speed dispersion and filtration.
[0091] 4. Prepare plasticizer, thickener, stabilizer, defoamer and solvent according to the proportion, grind, disperse at high speed and filter to obtain component 2 of hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0092] 5. The obtained component one and component two of the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure are evenly mixed, subjected to film-forming treatment, and then cured at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure.
[0093] The chlorinated rubber coating, the hexagonal boron nitride chlorinated rubber composite coating with no surface defect structure and the hexagonal boron nitride chlorinated rubber composite coating with rich surface defect structure prepared in Examples 1 to 6 were subjected to comprehensive performance testing, and the testing method was in accordance with "GB / T 13452.2-2008 Determination of film thickness of paint and varnish"; "GJB 150.11A-2009 Laboratory environmental test method for military equipment Salt spray test"; "GB / T 9286-2021 Cross-cut test of paint and varnish film"; the results are shown in Table 1.
[0094] Table 1 Test results
[0095] project Film thickness(μm) Corrosion resistance (96h) Adhesion(grade) Water contact angle (°) Embodiment 1 94 No bubbles, no shedding ≤1 54.1 Embodiment 2 96 No bubbles, no shedding ≤1 80.7 Embodiment 3 98 No bubbles, no shedding ≤1 100.7 Embodiment 4 95 No bubbles, no shedding ≤1 102.6 Embodiment 5 102 No bubbles, no shedding ≤1 99.7 Embodiment 6 100 No bubbles, no shedding ≤1 97.1
[0096] The above-mentioned embodiment 1 is a chlorinated rubber coating without adding hexagonal boron nitride two-dimensional nanomaterials, which is a blank control embodiment, and embodiment 2 is a chlorinated rubber coating with added hexagonal boron nitride two-dimensional nanomaterials without surface defect structure, and embodiment 3 to embodiment 6 are chlorinated rubber coatings with added hexagonal boron nitride two-dimensional nanomaterials with rich surface defect structure. The water contact angle in Table 1 can reflect the hydrophobicity of the chlorinated rubber coating. The larger the water contact angle, the better the hydrophobicity of the chlorinated rubber coating, and the smaller the water contact angle, the worse the hydrophobicity of the chlorinated rubber coating. From the data in Table 1, it can be seen that in embodiment 2 to embodiment 6, compared with embodiment 1, the water contact angle is significantly increased, reflecting that the chlorinated rubber coating with added hexagonal boron nitride two-dimensional nanomaterials according to the scheme of this embodiment has better hydrophobicity. Further, in embodiment 3 to embodiment 6, the water contact angle is significantly larger than that of embodiment 2, reflecting that the hydrophobicity of the chlorinated rubber coating with added hexagonal boron nitride two-dimensional nanomaterials with rich surface defect structure is better than that of the chlorinated rubber coating with added hexagonal boron nitride two-dimensional nanomaterials without surface defect structure.
[0097] In addition, see Figure 1 Schematic diagram of the morphology of hydrophobic hexagonal boron nitride two-dimensional nanomaterials. Figure 2 This is a schematic diagram of the element distribution of hydrophobic hexagonal boron nitride. The figure shows the distribution of nitrogen and boron elements in the hexagonal boron nitride material sample. Figure 3 This is a comparison of the microscopic morphology of hexagonal boron nitride with no surface defects and hexagonal boron nitride with rich surface defects. Figure 3 The left picture shows hexagonal boron nitride with no surface defects. Figure 3 The right picture in the figure shows hexagonal boron nitride with rich surface defects. Hexagonal boron nitride with rich surface defects has better hydrophobicity in chlorinated rubber coating. Figure 4 It is a schematic diagram of the contact angle of each embodiment of the above-mentioned embodiment 1 to the above-mentioned embodiment 6, Figure 4 (a) is the water contact angle of Example 1, which is 54.1°. Figure 4(b) The water contact angle of Example 2 is 80.7° Figure 4 (c) is the water contact angle of Example 3, which is 100.7°. Figure 4 (d) is the water contact angle of Example 4, which is 102.6°. Figure 4 (e) The water contact angle of Example 5 is 99.7°, Figure 4 (f) The water contact angle of Example 6 is 97.1°.
[0098] It should be clear that the present invention is not limited to the specific steps and structures described above. In addition, for the sake of brevity, detailed descriptions of known methods and technologies are omitted here.
[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hydrophobic hexagonal boron nitride chlorinated rubber composite coating, characterized in that: The preparation raw materials include: chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterials, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer and solvent; Among them, the mass ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoaming agent and the solvent is (80-100):(6-24):(20-40):(20-40):(20-60):(10-60):(20-50):(10-30):(10-50):(100-500).
2. The hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 1, characterized in that: The mass ratio of the chlorinated rubber resin, the hexagonal boron nitride two-dimensional nanomaterial, the hydroxymethyl acrylamide, the ethyl acrylate, the dispersant, the plasticizer, the thickener, the stabilizer, the defoamer and the solvent is 100:12:30:30:50:40:30:20:20:200, or 100:6:30:30:50:40:30:20:20:200, or 100:12:20:20:30:30:20:10:10:100, or 100:18: 40: 40: 60:50:40:30:30:300, or 100:24:30:30:50:40:30:20:20:
200.
3. The hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 1, characterized in that: The chlorinated rubber resin is a chlorinated rubber resin with a chlorine mass fraction of 66% to 68%, and the average relative molecular weight of the chlorinated rubber resin is 10,000 to 20,000; the dispersant is any one of polyethylene glycol 200 or polyethylene glycol 400 or a mixture thereof; the plasticizer is any one of dioctyl phthalate or dibutyl phthalate or a mixture thereof; the thickener is a mixture of methyl hydroxypropyl cellulose and bentonite; the stabilizer is any one of dibutyltin dilaurate or methyltin mercaptan or a mixture thereof; the defoamer is any one of a polyether defoamer or a silicone defoamer; and the solvent is any one of acetone, xylene, and ethyl acetate or a mixture of two or more combinations thereof.
4. The hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 3, characterized in that: The chlorinated rubber resin is a chlorinated rubber resin with a chlorine content of 66% to 68%, and the average relative molecular weight of the chlorinated rubber resin is 12000; the dispersant is composed of polyethylene glycol 200 and polyethylene glycol 400 in a mass ratio of 1:2; the plasticizer is composed of dioctyl phthalate and dibutyl phthalate in a mass ratio of 1:1; the thickener is composed of methyl hydroxypropyl cellulose and bentonite in a mass ratio of 1:1; the stabilizer is composed of dibutyltin dilaurate and methyltin mercaptan in a mass ratio of 1:2; the defoamer is a polyether defoamer; and the solvent is a mixture of acetone, xylene and ethyl acetate in a mass ratio of 3:2:
3.
5. A method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to any one of claims 1 to 4, characterized in that: Hexagonal boron nitride two-dimensional nanomaterial powder is used as a filler and compounded with chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate, dispersant, plasticizer, thickener, stabilizer, defoamer and solvent in a preset ratio to prepare composite coating component one and component two respectively. Component one and component two are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain a hydrophobic hexagonal boron nitride chlorinated rubber composite coating.
6. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 5, characterized in that: The hexagonal boron nitride two-dimensional nanomaterial powder is used as a filler, and is compounded with a chlorinated rubber resin, hydroxymethyl acrylamide, ethyl acrylate, a dispersant, a plasticizer, a thickener, a stabilizer, a defoamer, and a solvent according to a preset ratio to prepare a composite coating component one and a component two respectively, and the component one and the component two are mixed evenly, subjected to a film-forming treatment, and then cured at room temperature to obtain a hydrophobic hexagonal boron nitride chlorinated rubber composite coating, comprising: The chlorinated rubber resin, hexagonal boron nitride two-dimensional nanomaterial, hydroxymethyl acrylamide, ethyl acrylate and a dispersant are ground, dispersed at high speed and filtered to obtain a hexagonal boron nitride chlorinated rubber composite coating component 1; The plasticizer, thickener, stabilizer, defoamer and solvent are ground, dispersed at high speed and filtered to obtain the second component of the hexagonal boron nitride chlorinated rubber composite coating; The obtained hexagonal boron nitride chlorinated rubber composite coating component one and component two are mixed evenly, subjected to film-forming treatment, and then cured at room temperature to obtain the hexagonal boron nitride chlorinated rubber composite coating.
7. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 5, characterized in that: The preparation process of the hexagonal boron nitride two-dimensional nanomaterial powder is as follows: The hexagonal boron nitride precursor is obtained by hydrothermal synthesis with programmed temperature using ammonium borate and urea, after being treated with atmosphere protection and acid washing. The hexagonal boron nitride precursor is subjected to cell crushing and ultrasonic exfoliation, and by controlling the exfoliation time, hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure and hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure are obtained.
8. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 7, characterized in that: The method comprises: using ammonium borate and urea to perform temperature-programmed hydrothermal synthesis, and obtaining a hexagonal boron nitride precursor after atmosphere protection and acid washing process. The ammonium borate and urea are mixed, stirred evenly, placed in a stainless steel reactor, heated to 80-100°C, kept warm for 1-2 hours, then heated to 120-150°C, kept warm for 1-2 hours, heated to 160-180°C, introduced nitrogen, and the reaction product was pickled with hydrochloric acid to obtain a hexagonal boron nitride precursor.
9. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 8, characterized in that: The mass ratio of the ammonium borate to the urea is 2:
3.
10. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 7, characterized in that: The method of subjecting the hexagonal boron nitride precursor to cell crushing and ultrasonic exfoliation, and obtaining the hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure and the hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure by controlling the exfoliation time, comprises: Weigh the hexagonal boron nitride precursor and add it to a beaker, then add deionized water and isopropanol, use a stirrer to stir and mix evenly, seal the beaker mouth and place it in an ultrasonic cleaner for 1 to 2 hours to fully disperse the hexagonal boron nitride precursor powder. Place the beaker containing the uniformly mixed hexagonal boron nitride precursor dispersion in a cell crusher, and the total peeling time is 4 to 18 hours. The dispersion obtained by crushing and peeling is centrifuged at a speed of 5000r / min, and the upper clear liquid is taken to obtain a hexagonal boron nitride two-dimensional nanosheet dispersion, which is filtered and dried to obtain a hexagonal boron nitride two-dimensional nanomaterial powder.
11. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 10, characterized in that: The mass ratio of the hexagonal boron nitride precursor, the deionized water and the isopropanol is 1:(2-3):(2-3).
12. The method for preparing the hydrophobic hexagonal boron nitride chlorinated rubber composite coating according to claim 7, characterized in that: When the stripping time is controlled to be 6 hours or less, a hexagonal boron nitride two-dimensional nanomaterial powder with no surface defect structure is obtained; when the stripping time is controlled to be greater than 6 hours, a hexagonal boron nitride two-dimensional nanomaterial powder with rich surface defect structure is obtained.
Citation Information
Patent Citations
Method of utilizing urea assisted ultrasound to prepare hexagonal boron nitride nanosheet
CN107055491A
Chlorinated rubber anticorrosive paint and preparation method thereof
CN113881267A
Production of hexagonal boron nitride
JP1986168509A
Boron nitride powder and resin composition containing the same
JP2014166930A
Pigmented, Fine-Structured, Tribological Composite Material
US20140329729A1
